Plany : ustʹi︠a︡ ri︠e︡ki Taĭtiskii, ostrova Moneronʺ, bukhty Takmaka, Tunaĭchinskoĭ protoki, reĭda Poro-Tomari, i ozer na mysi︠e︡ Aniva / Kopirovalʺ khimicheskoi︠u︡ tushʹi︠u︡ K. Breĭtshprekherʺ - Russia. Glavnoe gidrograficheskoe upravlenīe (Sankt-Peterburg : Morskoe ministerstvo, Glavnoe gidrograficheskoe upravlenīe; [Санкт-Петербург] : Морское министерство, Главное гидрографическое управленіе, 1889)
Title translation: Plans : Mauka harbor, Busse Bay and Korsakov Post, on the southern half of the Sakhalin Island.; Relief shown by hachures and form lines. Depths shown by soundings and isolines.; Main title translation: Plans - mouth of the Taitiski River, Moneron Island, Takmak Bay, Tunaichinsky channel, Poro-Tomari anchorage, and lakes on Cape Aniva.; Top margin title translation: Eastern Sea, southern half of Sakhalin Island.; Maps: Planʺ ustʹi︠a︡ ri︠e︡ki Taĭtiski na W beregu O-va Sakhalina . -- Planʺ bukhty Takmaka na W beregu O-va Sakhalina . -- Planʺ reĭda Poro-Tomari . -- Planʺ ostrova Moneron -- Planʺ Tunaĭchinskoĭ rotoki . -- Planʺ ozer na Verkhneĭ chasti m-si︠a︡ Aniva.; "No. 370" -- handwritten bottom right margin Grayscale;